Sosialisasi dan Edukasi Kesehatan Reproduksi bagi Remaja di SMA Yapim Biru-Biru - Fahdi, Firdaus; Sari, Herviani; Manullang, Hengki Frengki; Sembiring, Bungamari (Jurnal Pengabdian Masyarakat Putri Hijau, 2024)
Adolescence is a critical period in a person's life, marked by significant physical, emotional, and social changes. Adequate knowledge about reproductive health is essential to help adolescents face these changes in a healthy and positive way. However, the spread of formal education and the stigma surrounding this topic often results in low understanding and risky behavior among teenagers. The "Reproductive Health Socialization and Education for Adolescents at SMA Yapim Biru Biru" program aims to increase students' knowledge and awareness regarding reproductive health, prevent health problems that may arise, and equip them with the correct information and skills needed to make healthy decisions . This program includes outreach activities, discussion groups, use of interactive media, and counseling sessions. Program results showed a significant increase in students' understanding of reproductive health, with 90% of students successfully answering more than 80% of the post-test questions correctly, compared to 65% who had low understanding on the pre-test. In addition, there have been positive changes in attitudes and behavior towards reproductive health, as well as a decrease in mitosis and misinformation among students. Feedback from students and teachers also shows that this program is effective and relevant to their needs. It has not only succeeded in achieving its goals but also provides recommendations for further, more in-depth programs, as well as involving parents to support adolescent reproductive health education. It is hoped that the results of this program can become a model that can be applied in other schools to improve the quality of reproductive health education among adolescents.